2022
DOI: 10.12973/eu-jer.11.4.2303
|View full text |Cite
|
Sign up to set email alerts
|

Soft Skills Through the Prism of Primary School Teachers

Abstract: <p style="text-align: justify;">COVID-19 and the expansion of distance learning pose new challenges to the educational system. Soft skills are imperative in this context, for children's effective and adaptive learning. The following study aims to discover teachers' representations by identifying their common conceptual framework of soft skills in primary school. Semi-structured interviews were conducted with teachers. The teachers' comments helped identify and define a framework of soft skills that would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…All respondents ranked "communication, time management, good attitudes, teamwork, self-discipline, presentation, and accountability" as the most important soft skills that candidates need to possess, whereas "market research, analysis, marketing, leadership, and customer service" have received low ratings and less importance. Ouchen et al (2022) shared the results obtained from primary school teachers' perceptions of the most important soft skills that should be developed. They found that the essential soft skills for children are intrapersonal skills such as critical thinking, and interpersonal skills like coexistence, tolerance, problem-solving, and learning to learn.…”
Section: Most Needed Soft Skills For Employabilitysupporting
confidence: 55%
“…All respondents ranked "communication, time management, good attitudes, teamwork, self-discipline, presentation, and accountability" as the most important soft skills that candidates need to possess, whereas "market research, analysis, marketing, leadership, and customer service" have received low ratings and less importance. Ouchen et al (2022) shared the results obtained from primary school teachers' perceptions of the most important soft skills that should be developed. They found that the essential soft skills for children are intrapersonal skills such as critical thinking, and interpersonal skills like coexistence, tolerance, problem-solving, and learning to learn.…”
Section: Most Needed Soft Skills For Employabilitysupporting
confidence: 55%
“…The research shows that the smart classroom is an emerging educational model that is progressively gaining popularity among teachers, who conceive and defend it as being an innovative and flexible model. In this respect, they highlight its potential to transform and renew the teaching and learning process, based on the establishment of powerful synergies between digital educational resources and the implementation of "active" teaching strategies [9,21]. This approach is in line with the hegemonic social discourse and is also reproduced in the recent academic literature, which emphasises the innovative possibilities offered by the smart classroom [8,17].…”
Section: Discussionmentioning
confidence: 78%
“…Educational resources [7][8][9][10][11][12][13][14][15][16] Teaching and learning practices [17][18][19][20][21] Roles [22] However, the focus of the academic literature on transformations in resources and practices does not transfer to other dimensions of great importance such as roles (which are less frequently studied) or to the axiological principles that guide activity in the smart classroom. Nevertheless, this model advocates a holistic restructuring of the traditional paradigm of pedagogical intermediation.…”
Section: Transformations Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…From the teacher's perspective, giving learners free rein over their emotions may seem non-constructive because it deviates from traditional didactic practices. Indeed, teachers often adopt generic conceptions of their role as facilitators of soft skills (Ouchen et al, 2022), whose job is to ensure the overall harmony of the class group. They may view this as synonymous with channeling the regulation of energies.…”
Section: Introductionmentioning
confidence: 99%